P55 Is Prescription Uptake And Medication Adherence Rating Scale (mars) A Useful Tool In Assessing Asthma Control In Children With Problematic Severe Asthma (psa)?. (10th November 2014) - Nagakumar, P; Hall, P; Bracken, M; Saglani, S; Bush, A; Fleming, L
Abstract : Introduction: Sub-optimal adherence to medications results in poor asthma control, however objective measurement of adherence is challenging. Aim: To assess adherence to inhaled corticosteroids (ICS) in children with problematic severe asthma (PSA) using prescription uptake and the Medicines Adherence Rating Scale (MARS) (self-reported adherence) and relate them to measures of asthma control. Methods: 160 patients assessed as part of the established RBH difficult asthma protocol (2008–2013) were included [[Arch Dis Child 2009;94:780–4]. Adherence was assessed using prescription uptake data (GP and local hospital) and MARS. Sub-optimal adherence was defined as a prescription uptake of <80%. Spirometry (FEV1 pre bronchodilator), bronchodilator reversibility (BDR), and exhaled nitric oxide (FENO) were measured. The Asthma Control Test (ACT), Paediatric Asthma Quality of Life Questionnaire (PAQLQ) was used to evaluate control. Number of courses of oral steroids and hospital admissions in the previous 12 months were recorded. Results: Median age was 11.6 yr (5–16). 66% were male. 52% had prescription uptake of <80%. MARS score showed only a weak correlation with prescription uptake (n = 48, r 2 =0.03, p = 0.29), even in patients with prescription uptake of <50% (n = 23, r 2 =0.09, p = 0.32). No relationship was found between prescription uptake and ACT, MARS, FEV1, rescue courses of OCS, FeNO or BDR (Table 1 ). Conclusion: Poor prescription uptake was not related to any measure of asthma control, meaning that we could not differentiate the genuine therapy resistant from the non-adherent. But it is not possible to assess how much ICS was actually inhaled. Patterns of ICS use may be a more important determinant of control. Self-reported adherence, as measured by MARS was high even in those with very poor <50%) prescription uptake highlighting the limitations of this questionnaire. More objective means of assessing adherence should be incorporated into protocols for assessing severe asthma.